A basic needs coaching paradigm for coaches of intercollegiate and high school athletes. Issue 3 (3rd July 2018) - Hook, Robert; Newland, Aubrey
ABSTRACT: Coaches play a pivotal role in guiding a positive experience for their athletes. Using Self-Determination Theory, this article proposes the Basic Needs Coaching Paradigm (BNCP) that guides coaches to fulfill athletes' three basic psychological needs of autonomy, competence, and relatedness, ultimately promoting an optimal sport experience for athletes. The BNCP incorporates theories and concepts from coaching science research into a palatable model for interested coaches to follow. Specific behavioral strategies for coaches are suggested in order to foster a mastery and caring climate, provide autonomy support for athletes, and develop practices to increase team cohesion.